Older adults use a prefrontal regulatory mechanism to reduce negative memory vividness of a highly emotional real-world event - Ford, Jaclyn H. (Neuroreport, 2018)
OBJECTIVES: Prior research has revealed an age-related shift in how individuals recall events from their personal past, with older adults reporting events that are more positive than young adults. We recently showed that age-by-valence interactions may be partially driven by a prefrontally-mediated control mechanism recruited by older adults during retrieval of negative laboratory events to reduce phenomenological richness. Specifically, age was associated with greater increases in prefrontal recruitment during retrieval of negative relative to positive events, with this recruitment linked to decreases in hippocampal activity and subjective vividness ratings. In the current study, we examined whether older adults may rely on a similar mechanism during retrieval of a complex, highly emotional real-world event. METHODS: Participants (n=58, ages 18–87) were presented with images related to the 2013 Boston Marathon Bombings and were asked to retrieve a memory associated with each image. Images cued participants with either negative (associated with fear, destruction, sadness) or positive (images of hope, resilience, support) features. RESULTS: This study replicated prior episodic memory tasks: age was associated with more negative hippocampal connectivity with dorsomedial prefrontal regions during retrieval of memories triggered by negative relative to positive cues. CONCLUSIONS: Such findings suggest that older adults may be recruiting a similar regulatory mechanism during retrieval of both negative laboratory stimuli and highly negative events from their past. These findings are discussed in relation to prior work showing that young and older adults interact differently with the negative details related to a highly negative event.